Role of Social Media as Communication Channel for Veterinary Extension Workers - Anbiah, Vigil; Vijayalakshmi, Ranganathan (Journal of Extension Education, 2018)
A study was conducted to assess the role of social media networks for effective digital communication among the veterinary extension workers. The study involved assessing the role and constraints of a social media group named as veterinary technical forum in the context of enhancing quality health service to the livestock by active networking with other experts of the world. It is concluded that the most important role of social media was the commonality of interest which could be achieved in sharing of knowledge. Lack of broadband services in remote locations was considered as the major constraints in adopting social media as a communication channel for veterinary extension works.